Biological drugs for the treatment of psoriasis in a public health system - Luciane Cruz Lopes; Miriam Sanches do Nascimento Silveira; Iara Alves de Camargo; Silvio Barberato-Filho; Fernando de Sá Del Fiol; Claudia Garcia Serpa Osorio- (Universidade de São Paulo, 2014)
OBJECTIVE To analyze the access and utilization profile of biological medications for psoriasis provided by the judicial system in Brazil. METHODS This is a cross-sectional study. We interviewed a total of 203 patients with psoriasis who were on biological medications obtained by the judicial system of the State of Sao Paulo, from 2004 to 2010. Sociodemographics, medical, and political-administrative characteristics were complemented with data obtained from dispensation orders that included biological medications to treat psoriasis and the legal actions involved. The data was analyzed using an electronic data base and shown as simple variable frequencies. The prescriptions contained in the lawsuits were analyzed according to legal provisions. RESULTS A total of 190 lawsuits requesting several biological drugs (adalimumab, efalizumab, etanercept, and infliximab) were analyzed. Patients obtained these medications as a result of injunctions (59.5%) or without having ever demanded biological medication from any health institution (86.2%), i.e., public or private health services. They used the prerogative of free legal aid (72.6%), even though they were represented by private lawyers (91.1%) and treated in private facilities (69.5%). Most of the patients used a biological medication for more than 13 months (66.0%), and some patients were undergoing treatment with this medication when interviewed (44.9%). Approximately one third of the patients discontinued treatment due to worsening of their illness (26.6%), adverse drug reactions (20.5%), lack of efficacy, or because the doctor discontinued this medication (13.8%). None of the analyzed medical prescriptions matched the legal prescribing requirements. Clinical monitoring results showed that 70.3% of the patients had not undergone laboratory examinations (blood work, liver and kidney function tests) for treatment control purposes. CONCLUSIONS The plaintiffs resorted to legal action to get access to biological medications because they were either unaware or had difficulty in accessing them through institutional public health system procedures. Access by means of legal action facilitated long-term use of this type of medication through irregular prescriptions and led to a high rate of adverse drug reactions as well as inappropriate clinical monitoring.